Development stage, storage temperature and storage duration influence phytonutrient content in cowpea (Vigna unguiculata L. Walp.). Issue 6 (June 2018) - Kirigia, Dinah; Winkelmann, Traud; Kasili, Remmy; Mibus, Heiko
Abstract: Cowpea ( Vigna unguiculata ) plays an important role in sustainable food security and livelihood improvement in Sub-Saharan Africa (SSA). The crop is rich in phytonutrients and minerals, which are key in solving malnutrition and hunger crisis, a major challenge in SSA. However, physiological status, storage temperature and duration affect phytonutrient levels and postharvest life of the leafy vegetable. Despite the significant importance of cowpeas, the maturity and postharvest storage effects on quality of the leafy vegetable remains unrevealed. The aim of this study was to analyze the dynamics of phytonutrients in cowpea leaves during development under field conditions in Kenya and in storage. The total carbohydrates (glucose, fructose, sucrose and starch) were highest at 90 d after planting (105.9 ± 2.5 g kg -1 ) compared to 30, 60 and 120 d. The total Phenolics (Gallic acid equivalents) increased gradually with age up to 12.0 ± 0.2 g kg -1 by 120 d. Catechin equivalent flavonoids, trolox equivalent antioxidants (TEA) and chlorophyll were highest in concentrations at 60 d after planting with 8.0 ± 0.5 g kg -1, 26.19 ± 0.5 g kg -1 and 5.7 ± 0.4 g kg -1, respectively. Quercetin equivalent flavonoids and total carotenoids did not show significant changes with age, while mineral concentration dynamics were specific for each element. Storage of cowpea leaves at room temperature (50–55 % relative humidity) led to a stronger decline of phytonutrients after 4 d, but mostly they remained stable at cold storage (5 °C). Results of this study highlight the importance of developmental stage at harvest, storage conditions and duration for the optimal availability of phytonutrients in freshly consumed leaves and for postharvest management strategies.